Factors Affecting Tourist Interest on Sharia Tourism - Popon Srisusilawati (al-Uqud : Journal of Islamic Economics, 2020)
Sharia tourism is part of the halal industry which becomes one of the major supporters of the sharia economy in Indonesia. Nevertheless, since 2011, the city of Bandung as the epicentrum of sharia tourism experienced a decreasing number of visitors. The purpose of this study is to analyze the factors that influence tourist interest in visiting sharia tourism destinations. The research method is quantitative. The results of this study indicate that service, safety, and tourism influence tourist interest. The safety and promotion factors significantly influence tourist interest in visiting Sharia tourism, while service has no significant effect on tourist interest.